2017
DOI: 10.1155/2017/8631945
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Compliance with Nutritional Counselling on Body Composition Parameters in Head and Neck Cancer Patients under Radiotherapy

Abstract: Background. Radiotherapy (RT) has been associated with increased risk of malnutrition in cancer patients, particularly in those with head and neck cancer (HNC). The aim of this prospective study was to evaluate the effects of compliance of patients with individual dietary counselling on body composition parameters in HNC patients under RT. Material and Methods. Sixty-nine consecutive patients (mean age: 61.0 ± 13.8) were prospectively followed. Bioelectrical impedance analysis (BIA) was performed to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 28 publications
4
40
0
8
Order By: Relevance
“…Weight loss is accompanied by loss of FFM, SM, and BCM, deterioration in the QOL, more severe treatment-induced toxicity, and a shorter survival. 17 Furthermore, this study also demonstrated the beneficial value of FFMI in helping diagnose malnutrition and the association of decreased FFMI with impaired QOL, which can partially support the important role of body composition parameters in nutritional assessment.…”
Section: Discussionsupporting
confidence: 60%
“…Weight loss is accompanied by loss of FFM, SM, and BCM, deterioration in the QOL, more severe treatment-induced toxicity, and a shorter survival. 17 Furthermore, this study also demonstrated the beneficial value of FFMI in helping diagnose malnutrition and the association of decreased FFMI with impaired QOL, which can partially support the important role of body composition parameters in nutritional assessment.…”
Section: Discussionsupporting
confidence: 60%
“…The cut-off points for critical weight loss during RT were based on the international consensus statement of the Academy of Nutrition and Dietetics and the American Society for Parenteral and Enteral Nutrition [11]. A HNC patient should be weighed routinely, since any weight loss >5% (compared to their usual weight or healthy weight over six months) is a factor contributing to a poor prognosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Further qualitative research is recommended to investigate these barriers in depth, as they are potentially modifiable and can be addressed. Improving adherence to dietary recommendations has been shown to result in improved outcomes both within this study and others (Capuano et al, 2008, Hopanci Bicakli et al, 2017. The characteristics of this patient population also suggest that adherence may be particularly challenging given the high rate of mental health problems, substance use and social issues which increases psychologic distress and depression (Kugaya et al, 2000, DiMatteo, Lepper, & Croghan, 2000.…”
Section: Additional Analysissupporting
confidence: 57%
“…However this did not account for adherence to the dietary advice actually provided. This has been addressed more recently, where a study defined adherence to dietary counselling as consuming ≥75% of recommended energy and protein intake, and this confirmed favourable outcomes on body composition parameters with adherence (Hopanci Bicakli et al, 2017).…”
Section: Introductionmentioning
confidence: 97%